Multifunctional cellulose-paper for light harvesting and smart sensing applications - Vicente, António T. (2019)
PTDC/CTM-ENE/5125/2014 PTDC/CTM-NAN/2912/2014 SFRH/BPD/115566/2016 SFRH/BPD/114833/2016